2008
DOI: 10.1007/s11517-008-0332-0
|View full text |Cite
|
Sign up to set email alerts
|

Tensile radial stress in the spinal cord related to arachnoiditis or tethering: a numerical model

Abstract: Spinal arachnoiditis comprises fibrous scarring of the subarachnoid space, following spinal trauma or inflammation, and is often associated with syringomyelia. We hypothesised that cord-to-dura attachments could cause transient tensile cord radial stress, as pressure waves propagate. This was tested in a fluid-structure interaction model, simulating three types of cord tethering, with 'arachnoiditis' confined to a short mid-section of the cord. The annular system was excited abdominally with a short transient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…There is currently no experimental data available on the permeability of arachnoiditis within the SAS, and the range of values used here is based on previous numerical studies (Bilston et al, 2008). A conservative (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently no experimental data available on the permeability of arachnoiditis within the SAS, and the range of values used here is based on previous numerical studies (Bilston et al, 2008). A conservative (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…hydrocephalus; Gupta et al, 2010;Cheng et al, 2009), including syringomyelia. Both analytical (Carpenter et al, 2003;) and numerical (computational fluid dynamics) models of the spinal subarachnoid space have been reported (Loth et al, 2001;Bilston et al, 2006;Bertram et al, 2008;Sweetman and Linninger, 2011). To the best of our knowledge, no studies have yet demonstrated how arachnoiditis disturbs CSF hydrodynamics in the spinal subarachnoid space (SAS) in a realistic three-dimensional human geometry and this may contribute to our understanding of syrinx formation.…”
Section: Introductionmentioning
confidence: 99%
“…As in previous modelling (Bertram et al, 2008(Bertram et al, , 2005, the finite-element fluid/structure-interaction code ADINA (ADINA R&D Inc., Watertown, MA, USA) was applied to create a fully interactive model of the CSF in the SAS, contained by the dura mater and its surroundings, with the SAS fluid in turn surrounding the spinal cord. The model…”
Section: Anatomic Modelmentioning
confidence: 99%
“…[16][17][18] Numerous studies on the distribution of spinal cord deformations at the moment of injury were conducted in the past. [3,5,[19][20][21][22] According to our knowledge there was no clinical study describing critical values of mechanical stress and strain for the cervical spinal cord performed previously.…”
Section: Introductionmentioning
confidence: 99%